Home Fare Advantage: An examination of the Role of Food and Beverages in Mercedes-Benz Stadium’s Event Experience - Mark A. Slavich; Gregg Rich; Dylan Williams (Journal of Applied Sports Management, 2022)
Through the lens of Expectation Disconfirmation Theory and with consideration of other event experience factors, our study examines how strategic concessions changes implemented by the Arthur M. Blank (AMB) Group with the building of Mercedes-Benz Stadium affect the fan experience at its professional sport events. These changes differ significantly from operational practices at most sport venues, with emphasis on eliminating bottlenecks to increase throughput and allowing for reduced costs without negatively affecting quality. Data were collected through an online survey of Atlanta United match attendees and an online observation. Results from this study suggest that management prioritization of concession services may be the most effective approach for engendering positive, overall event experiences from patrons.
Keywords: sport experience; food and beverages; satisfaction